Combination therapies induce cancer cell death through the integrated stress response and disturbed pyrimidine metabolism. Issue 4 (5th March 2021) - Hartleben, Goetz; Schorpp, Kenji; Kwon, Yun; Betz, Barbara; Tsokanos, Foivos‐Filippos; Dantes, Zahra; Schäfer, Arlett; Rothenaigner, Ina; Monroy Kuhn, José Manuel; Morigny, Pauline; Mehr, Lisa; Lin, Sean; et al.
Abstract: By accentuating drug efficacy and impeding resistance mechanisms, combinatorial, multi‐agent therapies have emerged as key approaches in the treatment of complex diseases, most notably cancer. Using high‐throughput drug screens, we uncovered distinct metabolic vulnerabilities and thereby identified drug combinations synergistically causing a starvation‐like lethal catabolic response in tumor cells from different cancer entities. Domperidone, a dopamine receptor antagonist, as well as several tricyclic antidepressants (TCAs), including imipramine, induced cancer cell death in combination with the mitochondrial uncoupler niclosamide ethanolamine (NEN) through activation of the integrated stress response pathway and the catabolic CLEAR network. Using transcriptome and metabolome analyses, we characterized a combinatorial response, mainly driven by the transcription factors CHOP and TFE3, which resulted in cell death through enhanced pyrimidine catabolism as well as reduced pyrimidine synthesis. Remarkably, the drug combinations sensitized human organoid cultures to the standard‐of‐care chemotherapy paclitaxel. Thus, our combinatorial approach could be clinically implemented into established treatment regimen, which would be further facilitated by the advantages of drug repurposing. Synopsis: This study identifies novel combinatorial drug treatments to induce death of different tumor cells, and defines the mechanisms of synergism between a mitochondrial uncoupler and antidepressants or dopamine receptor antagonists. Mitochondrial uncoupler NEN synergized with tricyclic antidepressants (TCAs) and dopamine receptor antagonists to induce tumor cell death. Synergistic cell death relied on the induction of the integrated stress response pathway and the catabolic CLEAR network. Combinatorial drug treatment sensitized human pancreatic cancer organoids to Paclitaxel chemotherapy. Abstract : This study identifies novel combinatorial drug treatments to induce death of different tumor cells, and defines the mechanisms of synergism between a mitochondrial uncoupler and antidepressants or dopamine receptor antagonists.